Working in the New Low‐Wage Economy: Understanding Participation in Low‐Wage Employment in the Recessionary Era. Issue 1 (March 2015) - Visser, M. Anne; Meléndez, Edwin
Abstract : This paper examines the factors that influence the likelihood of engaging in low‐wage work during the recessionary and post‐recessionary era. Using micro data from the 5‐year 2008–2012 American Community Survey Estimates, we examine human capital, structural, and labor market characteristics that induce workers' participation into low‐wage jobs and labor markets, as well as how these vary between and within various ethnic/racial, age, and gender groups, including Hispanic/Latino ethnic groups. We find that the factors influencing engagement in low‐wage employment largely mirror those identified in pre‐recessionary studies and analyses but that there is a differential effect across ethnicity, race, gender, and age that may lead to and lock specific groups of workers into low‐wage employment. Using a post‐estimation technique to generate predicted probabilities, we discuss how these factors influence a worker's likelihood to engage in low‐wage employment across and within ethnic and racial populations, and the implications these present for contemporary scholarship, policy, and praxis.